An outbreak of Clostridium difficile infections due to new PCR ribotype 826: epidemiologic and microbiologic analyses. (March 2018) - Crobach, M.J.T.; Voor in 't holt, A.F.; Knetsch, C.W.; van Dorp, S.M.; Bras, W.; Harmanus, C.; Kuijper, E.J.; Vos, M.C.
Abstract: Objectives: To investigate an unusual outbreak of five patients with a total of eight episodes of a Clostridium difficile infection on a gastrointestinal surgical ward of a Dutch tertiary-care, university-affiliated hospital. Methods: Clinical case investigations and laboratory analyses were performed. Laboratory analyses included PCR ribotyping, multiple-locus variable-number tandem repeat analysis typing, toxin typing, antimicrobial susceptibility testing and whole genome sequencing. Results: The outbreak was associated with recurrent and severe disease in two of five patients. All episodes were due to a unique ribotype that was not recognized in the collection of an international network of reference laboratories and was assigned PCR ribotype 826. PCR ribotype 826 is a toxin A–, toxin B– and binary toxin–positive ribotype which according to molecular typing belongs to clade 5 and resembles the so-called hypervirulent ribotype 078. The presence of a clonal outbreak was confirmed by whole genome sequencing, yet the source of this newly identified ribotype remained unclear. Conclusions: This newly identified C. difficile PCR ribotype 826 is part of clade 5 and might also have increased virulence. The recognition of this outbreak highlights the need for ongoing C. difficile infection surveillance to monitor new circulating ribotypes with assumed increased virulence.